2022
DOI: 10.3389/fevo.2022.1007599
|View full text |Cite
|
Sign up to set email alerts
|

The diadromous watersheds-ocean continuum: Managing diadromous fish as a community for ecosystem resilience

Abstract: Diadromous fishes play important ecological roles by delivering ecosystem services and making crucial connections along the watersheds-ocean continuum. However, it is difficult to fully understand the community-level impacts and cumulative benefits of diadromous fish migrations, as these species are most often considered individually or in small groups. Their interactions at a community level (e.g., interdependencies such as predation, co-migration, and habitat conditioning) and the connections between their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 222 publications
0
5
0
Order By: Relevance
“…This approach has similarly been adopted in the recovery plans for other anadromous fishes, such as the endangered Coho salmon in California [ 76 ]. Furthermore, restoring aquatic connectivity for river herring spawning migrations can help recover additional ecological functions and ecosystem services along the ecosystem gradient of the watershed-ocean continuum [ 77 ]. River herring serve as forage prey for other birds, mammals, fish like the recreationally valuable striped bass, while transporting nutrients from the marine environment into freshwater ecosystems [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach has similarly been adopted in the recovery plans for other anadromous fishes, such as the endangered Coho salmon in California [ 76 ]. Furthermore, restoring aquatic connectivity for river herring spawning migrations can help recover additional ecological functions and ecosystem services along the ecosystem gradient of the watershed-ocean continuum [ 77 ]. River herring serve as forage prey for other birds, mammals, fish like the recreationally valuable striped bass, while transporting nutrients from the marine environment into freshwater ecosystems [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our study suggested that global approaches such as the regional and coast‐wide initiative conducted by the Atlantic States Marine Fisheries Commission in the last benchmark stock assessment (ASMFC, 2020) may be widely beneficial to management. While most management actions are still directed locally, actions at national and global scales are required to mitigate the climate change effect on species stocks (Kritzer et al, 2022; Ouellet et al, 2022). GR3D explicitly integrates range‐limit processes such as dispersal and enables us to forecast how changing conditions may affect population dynamics since multiple processes are influenced by temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The Atlantic salmon Endangered Species Act listing is unique in recognizing the need for recovery of the full diadromous community as critical to recovery. Additionally, recent work suggests that the ecosystem services provided by diadromous fish collectively are important to climate resilience across river, estuary, and ocean habitats [120].…”
Section: Plos Climatementioning
confidence: 99%
“…Projects arising through these efforts include two noted in Section 6.2 associated with Atlantic salmon: a range-wide analysis of existing and projected habitat conditions for Atlantic salmon and baseflow mapping across Maine watersheds [104]. Synthesis work on diadromous fish communities and ecosystem interactions of these twelve species was also completed [120]. It describes the structure and function of diadromous fish communities in freshwater ecosystems, synthesizes species ecosystem roles and interactions in the U. S. NES, and discusses changing environmental conditions in rivers, estuaries, and the coastal ocean.…”
Section: Watersheds and Estuariesmentioning
confidence: 99%